The sixth extinction [compact disc, unabridged] : an unnatural history - Kolbert, Elizabeth (Audioworks, 2014)
Provides an account of the disappearances occurring all around us and traces the evolution of extinction as concept, from its first articulation by Georges Cuvier in revolutionary Paris up through the present day. The sixth extinction is likely to be mankind's most lasting legacy, compelling us to rethink the fundamental question of what it means to be human.